Serum levels of macrophage migration inhibitory factor and interleukin 17 in patients with nonsegmental vitiligo - Osama S Sorour; Eman S Nassar; Somaya M Eldin Ahmed; Carmen I Farid (Wolters Kluwer Medknow Publications, 2020)
Introduction Immunological mechanisms definitely play a role in melanocyte loss in vitiligo. Several cytokines are involved in the regulation of immune cell stimulation and functional characterization. Interleukin 17 (IL-17) and macrophage migration inhibition factor (MIF) are among the cytokines reportedly involved in the pathogenesis of many other autoimmune diseases. Reports of upregulation of their serum level have been made in patients with vitiligo. Objective To evaluate the serum levels of MIF and IL-17 in patients with nonsegmental vitiligo and their relation to the occurrence and progression of the disease. Patients and methods This case-control study was conducted on 40 patients having nonsegmental vitiligo, of which 24 had active progression of the disease during the past 3 months, whereas the rest had a stable course over a year. Serum levels of IL-17 and MIF as determined by ELISA were compared among patients with those of 40 healthy controls. Their relations to disease severity (as determined by vitiligo area scoring index score), extent (as determined by body surface area of involvement), and activity were studied. Results Serum IL-17 and MIF were significantly higher in patients with vitiligo than in controls, with no significant difference between those with progressive or stable course. Both correlated positively with disease extent and severity in all patient groups. A highly significant positive correlation was found between serum IL-17 and MIF levels in all patient groups. Conclusion IL-17 and MIF contribute to vitiligo pathogenesis and could serve as indicators of disease extent and severity but not activity.